Blood Glutamate Levels Are Closely Related to Acute Lung Injury and Prognosis after Stroke - Bai, Wei; Li, Wei; Ning, Ya-Lei; Li, Ping; Zhao, Yan; Yang, Nan; Jiang, Yu-Lin; Liang, Ze-Ping; Jiang, Dong-Po; Wang, Ying; Zhang, Meng; Zhou, Yuan-Guo (Frontiers in Neurology, 2018)
Background Acute lung injury (ALI) is a serious complication of stroke that occurs with a high incidence. Our preclinical results indicated that ALI might be related to blood glutamate levels after brain injury. The purpose of this study was to assess dynamic changes in blood glutamate levels in patients with stroke and to determine the correlation between blood glutamate levels, ALI, and long-term prognosis after stroke. Methods Venous blood samples were collected from controls and patients with stroke at admission and on the third and seventh day after the onset of stroke. Patients were followed for 3 months. The correlations among blood glutamate levels, severities of stroke and ALI, and long-term outcomes were analyzed, and the predictive values of blood glutamate levels and severity scores for ALI were assessed. Results In this study, a total of 384 patients with stroke were enrolled, with a median age of 59 years. Patients showed significantly increased blood glutamate levels within 7 days of stroke onset (p < 0.05), and patients with more severe injuries showed higher blood glutamate levels. Moreover, blood glutamate levels were closely related to the occurrence (adjusted odds ratio, 3.022, p = 0.003) and severity (p < 0.001) of ALI and the long-term prognosis after stroke (p < 0.05), and they were a more accurate predictor of ALI than the more commonly used severity scores (p < 0.01). Conclusion These results indicated that an increased blood glutamate level was closely related to the development of ALI and a poor prognosis after stroke. Clinical Trial Registration http://www.chictr.org.cn, identifier ChiCTR-RPC-15006770.